Breaking the HFEM public key scheme - Chun-sheng GU (Tongxin xuebao)
To design post-quantum public key cryptography, Zhao,et al presented a novel public key scheme based on the BMQ problem. An equivalent secret key could directly be solved from the public key of their scheme by applying the property of the ergodic matrix over finite field. Thus, the HFEM public key scheme was broken.